Un enfoque espacial para el estudio arqueológico de las relaciones de dependencia asimétrica basada en recursos esenciales: el caso de las tierras bajas mayas del sur - Graf, Paul (2024)
Asymmetrical dependencies and social relations are generally difficult to demonstrate in the archaeological record, especially in societies with limited or no written evidence, and in geographic zones with high levels of decomposition. The Classic Maya of the southern lowlands in Mesoamerica were subject to both problems. In order to reconstruct a representative image of the settlement landscape during the Late Classic period, an integrated set of field methods was implemented at the archaeological site Tzikin Tzakan in the Peten region of Guatemala between 2021 and 2023. GIS analyses, such as least cost path and viewshed, allowed the study of dependency mechanisms based on essential resources, taking into account physical barriers, environmental risks and moral-ideological constraints. This article presents preliminary results and implications on the spatial relationships and social entanglements between different actors in the ancient community of Tzikin Tzakan.